A feasibility study of the use of virtual reality relaxation in an NHS inpatient neurorehabilitation unit - Edwards, Laura (Frontiers in Virtual Reality, 2025)
ObjectiveTo assess the feasibility of delivering a virtual reality relaxation intervention on an inpatient neurorehabilitation unit within the NHS.MethodsAn open-label feasibility study. Participants undergoing inpatient neurorehabilitation were recruited to use a virtual-reality distraction intervention under the guidance of a clinician with a minimum of one session per participant and no upper limit. The main outcome measures were around recruitment and retention, acceptability, pain, and anxiety.ResultsRecruitment was lower than anticipated due to many potential participants not meeting inclusion criteria. Nine participants were recruited and used the intervention a total of 23 times. Pain and anxiety scores were statistically significantly reduced (p = 0.0039 for both). Participants enjoyed using the VR. No serious adverse events were noted.ConclusionVirtual reality relaxation is enjoyable and successfully reduced pain and anxiety scores in patients on our neurorehabilitation unit, but only few neurorehabilitation inpatients were eligible for this study.